Kombinasi Metode VIKOR dan Rank Order Centroid Dalam Pemilihan E-Marketplace - Ahmadi Irmansyah Lubis; Umri Erdiansyah; Mukhlis Ramadhan (STMIK Budi Darma, 2022)
In a situation that is still being hit by the COVID19 Pandemic until now, it has an impact on the way people meet the needs of life, both primary and secondary needs. In one case, the pandemic also affected the shopping patterns of people who required them to shop online in order to reduce activities outside the home. So in this study the authors conducted research on the topic of Decision Support Systems in the selection of E-Marketplace. In this case, the author applies the VIKOR and Rank Order Centroid methods in assessing several sites or applications that are generally used by the public in online shopping activities. The alternatives used are Shopee, Lazada, Tokopedia, Bukalapak and Facebook Marketplace. For the criteria used, namely by using an assessment based on the User Interface, Product Completeness, Service Response, Transaction Process, and Delivery Service. The test results obtained are based on the calculation of the VIKOR method and the Rank Order Centroid against the alternatives and criteria used, Shoopee as the best alternative by obtaining a VIKOR index value of 1. Thus, it can be seen that the VIKOR method and Rank Order Centroid has been successfully applied to the recommendation system for marketplace selection.